2021
DOI: 10.1186/s13071-021-04737-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the suitability of mitochondrial and nuclear DNA genetic markers for molecular systematics and species identification of helminths

Abstract: Background Genetic markers are employed widely in molecular studies, and their utility depends on the degree of sequence variation, which dictates the type of application for which they are suited. Consequently, the suitability of a genetic marker for any specific application is complicated by its properties and usage across studies. To provide a yardstick for future users, in this study we assess the suitability of genetic markers for molecular systematics and species identification in helmint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 77 publications
(30 reference statements)
3
39
0
Order By: Relevance
“…Our findings corroborate previous studies, as successful discrimination of nematode species within the Angiostrongylus cantonensis lineage was also attained using these two genetic markers [ 28 ]. More recently, the suitability of the mitochondrial 12S and 16S rRNA genes for molecular identification of parasitic trematodes, cestodes, and nematodes were ascertained through comparisons with other genetic markers [ 36 ]. Although the mitochondrial rRNA genes are generally the most conserved of the genes in the mitochondrial genome, here we provide evidence of the ability of the mitochondrial genes as alternative genetic markers for molecular identification of trematodes, instead of the commonly used mitochondrial protein-coding genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings corroborate previous studies, as successful discrimination of nematode species within the Angiostrongylus cantonensis lineage was also attained using these two genetic markers [ 28 ]. More recently, the suitability of the mitochondrial 12S and 16S rRNA genes for molecular identification of parasitic trematodes, cestodes, and nematodes were ascertained through comparisons with other genetic markers [ 36 ]. Although the mitochondrial rRNA genes are generally the most conserved of the genes in the mitochondrial genome, here we provide evidence of the ability of the mitochondrial genes as alternative genetic markers for molecular identification of trematodes, instead of the commonly used mitochondrial protein-coding genes.…”
Section: Discussionmentioning
confidence: 99%
“…The NAD1 gene is popular among family Echinostomatidae, and successful molecular discrimination among the morphologically similar Echinostoma revolutum species complex have been achieved [ 43 47 ]. Additionally, the NAD1 gene showed higher levels of inter species variation compared to the COI gene within Echinostoma and among trematodes [ 36 , 43 ]. Similar to the COI gene, although they are useful for species discrimination, the high sequence variatblity can be a limiting factor hindering amplification of broad species range.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on the mitochondrial genome due to its utility in taxonomic resolution. Mitochondrial DNA evolves faster compared to nuclear genetic markers, generating a higher degree of sequence variation which makes it useful to resolve lower taxonomic levels for organisms ( Chan et al 2021 , Hassanin et al 2013 ). Furthermore, the relatively small size of the mitogenome (~ 16,000 base pairs long) makes it a practical alternative as a molecular marker.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, single nucleotide polymorphisms (SNPs) and microsatellites exhibit high polymorphism amongst populations or individuals ( Galbusera et al 2000 , Jiang et al 2016 ). In addition, the highly-conserved nature of nuclear rRNA gene sequences makes it suitable for resolving higher taxonomic levels for organisms ( Chan et al 2021 ). Other studies have shown that combining mitochondrial and nuclear DNA analysis provided better taxonomic resolution ( Abreu et al 2020 , Lambret-Frotté et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The easy readout of the entire mtDNA sequence by single egg RNA-sequencing provides valuable insight into the regional transmission and spread of T . solium infections, because the “barcodes” of mitochondrial genes can be easily used for taxonomic fine tuning [ 45 , 46 ] and thus for elucidation of chains of infection.…”
Section: Discussionmentioning
confidence: 99%